Temporal Trends Over a Decade of Defibrillator Therapy for Primary Prevention in Community Practice. (18th April 2017) - BOVEDA, SERGE; NARAYANAN, KUMAR; JACOB, SOPHIE; PROVIDENCIA, RUI; ALGALARRONDO, VINCENT; BOUZEMAN, ABDESLAM; BEGANTON, FRANKIE; DEFAYE, PASCAL; PERIER, MARIE‐CÉCILE; SADOUL, NICOLAS; PIOT, OLIVIER; KLUG, DIDIER; et al.
Temporal Trends Over a Decade of Defibrillator Therapy: Background: Technology and clinical practice surrounding the use of the primary prevention implantable cardioverter defibrillator (ICD) are in a state of constant evolution. The purpose of the study was to test the hypothesis of significant temporal trends in characteristics and outcomes over a decade of ICD therapy. Methods: Between 2002 and 2012, 5, 539 consecutive patients (age 62.5 ± 11 years, 84.9% male), with ischemic or nonischemic cardiomyopathy, implanted with a primary prevention ICD from 12 centers in France were included. Information on characteristics and outcomes (including causes of death) were evaluated over a median follow‐up of 994 days (466‐1, 667). Results: In addition to a shift in the type of devices implanted with a significant increase in cardiac resynchronization therapy‐defibrillator (CRT‐D) over time (43.6 to 60.4%, P = 0.0001), an increase in mean age (from 61.5 ± 11.6 to 63.2 ± 10.9 years, P = 0.0016), proportion of nonischemic cardiomyopathy (31.0 to 44.7%, P <0.0001) and women recipients (11.4 to 15.8%, P = 0.004) was observed. A total of 1, 181 patients (22.3%) received ≥1 appropriate therapy, inappropriate therapies occurred in 355 patients (6.7%) and 826 patients (15.2%) died, mainly from cardiovascular causes (49.3%). Annual mortality incidence (5.4% to 4.3%, P = 0.05), as well as incidence of appropriate therapy (10.4% to 7.1%, P = 0.0004), significantly decreased over the decade. By contrast, incidence of ICD‐related late (>30 days after implant) complications significantly increased (4.6 to 7.6%, P = 0.003). Conclusion: Our findings demonstrate significant changes in patterns of use and outcomes in primary prevention ICD over the last decade with reductions in mortality and appropriate therapies, counterbalanced by an increase in complications.